A comparison between the modern hydro distillation technique and microwave extractor in extracting lignans from phyllanthus niruri - Kritiga Shankar, Murugesan (2012)
Phyllanthus Niruri (Pokok Dukung Anak) can produce essential oil that is important in medicine and also important in developing our agriculture sector nowadays. To obtain Phyllanthus Niruri essential oil, entrepreneur and researcher nowadays use various extraction methods. So the objective of this study is to obtain lignin, a major component of essential oil from Phyllanthus Niruri plant source by comparing two different extraction methods which are modem hydro distillation technique and microwave extractor. The extraction process Aas conducted at three different temperatures which were 30°C, 80 0 C and 100°C. The power for the microwave extractor is set at 1000 W for all the temperatures. The raw materials were cut into small pieces and ethanol was used as extraction solvent in both methods. The weight for each run was fixed at 250g of samples. After the extraction process was completed, the samples were processed in rotary evaporator and water bath in order to separate the solvents from the oil. The weight of oil was recorded and calculations were performed to compare the efficiency yield. Finally all the samples were analyzed using Gas Chromatography Mass Spectrometer (GC-MS). The results showed that of all the six samples, lignin was detected only at temperature 30°C by using hydro distillation as the extraction method. This indicates that lignin is a highly volatile oil and the most suitable method to extract ligin is by hydro distillation method.